Validation of the Polar Team Pro system for sprint speed with ice hockey players - Conners, R. T.; Whitehead, P. N.; Dodds, F. T.; Schott, K. D.; Quick, M. C. (The Journal of Strength and Conditioning Research, 2022)
Commercially available player tracking sensors such as the Polar Team Pro system (PTPS) have been used to monitor athlete performance. Use during ice hockey practices and games has resulted in seemingly plausible and valid values for internal metrics (heart rate); however, external metrics (distance, speed, and acceleration) seem sporadic and counterintuitive. To determine the validity of the PTPS for measuring sprint speed with collegiate hockey players, 15 NCAA Division I male athletes (21.86 ± 1.04 years, 175.86 ± 6.78 cm, 80.58 ± 4.44 kg) participated in the study. Subjects wore a PTPS strap, at the level of the xiphoid process, and performed 2 sprints of 15.24 m (blue line to blue line) and 35.05 m (red line to the far blue line) in 3 conditions: indoor ice skating, indoor running, and outdoor running. Timing gates (TG) were used to determine sprint times, which allowed for manual calculation of speed. Speed values from the PTPS and TG were compared using paired-samples t-tests, and an alpha level of 0.05, 2-sided, was set a priori as a significance level. For indoor ice skating, PTPS significantly underestimated speeds at both distances (p < 0.001). However, PTPS significantly overestimated speeds for indoor and outdoor sprints at both distances (p = 0.001). The PTPS is not accurate for measuring short-distance linear sprint speed or linear sprint speed during indoor ice skating. The inconsistency in speed values needs to be taken into consideration when using the system for science-based training because inaccurate speed values may negatively affect other external performance metrics provided by PTPS.